2007
DOI: 10.1111/j.1540-8159.2007.00884.x
|View full text |Cite
|
Sign up to set email alerts
|

Pacemaker Infection Secondary to Burkholderia Pseudomallei

Abstract: Infection is a relatively rare but devastating complication of intracardiac device implantation. Burkholderia pseudomallei is the organism which causes melioidosis, an endemic and lethal infection in the tropics. We describe a case of pacemaker infection secondary to Burkholderia pseudomallei, which was treated by explantation of the device and appropriate antimicrobial therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…15 articles, with a total of 29 patients were excluded due to insufficient clinical information (n = 12) [ 1 , 3 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ] or no report of microbiological diagnosis (n = 3) [ 21 , 22 , 23 ]. A total of 31 articles [ 5 , 10 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ] with 41 patients met the inclusion criteria of this systematic review. We did not exclude articles based on language, although only English-language articles were identified by our search strategy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…15 articles, with a total of 29 patients were excluded due to insufficient clinical information (n = 12) [ 1 , 3 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ] or no report of microbiological diagnosis (n = 3) [ 21 , 22 , 23 ]. A total of 31 articles [ 5 , 10 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ] with 41 patients met the inclusion criteria of this systematic review. We did not exclude articles based on language, although only English-language articles were identified by our search strategy.…”
Section: Resultsmentioning
confidence: 99%
“…Whitmore was the first to describe endocarditis in melioidosis in 1913, reporting a 39–year–old male with small left-sided valvular vegetations post-mortem. In our systematic review, there were 11 patients with endocarditis reported in the literature [ 1 , 5 , 17 , 19 , 24 , 25 , 26 , 27 , 28 ]; six had adequate data for inclusion [ 5 , 24 , 25 , 26 , 27 , 28 ]. All six patients were males with an age range between 29 to 73 years and a mean age of 55.7 years.…”
Section: Resultsmentioning
confidence: 99%